The Function of Honorific Term Ité: Cultural Perspectives from Manggarai, Indonesia - Menggo, Sebastianus (Journal of Language and Literature, 2024)
Culture pertains to human existence and encompasses the various aspects of a civilization’s way of life. On the other hand, language refers to the complex communication system employed by individuals inside a specific culture or group. Language utilization typically represents the societal customs, cognitive processes, cognitive functioning, historical context, and interconnections within a given human civilization. Utilizing the inclusive personal pronoun "ité" in the Manggarai language facilitates identifying a connection between linguistic elements and cultural principles. This study examines the relationship between the two specified elements, particularly emphasizing the arguments offered. The data were obtained using observations and interviews conducted with fifteen traditional representatives. Subsequently, a qualitative analysis was performed on the collected data. The findings suggest that its utilization in its various manifestations indicates the cultural norms and customs observed by those living in the Manggarai region of Indonesia. Based on the presented data, this study asserts that the first personal pronoun plural inclusive "ité" in the Manggarai language and culture serves as a means for the speaker to communicate politeness and humility towards the hearer or listener. It signifies a genuine respect for the interlocutor, particularly when they hold a high position. In addition, ité shows familiarity, brotherhood, and sincerity in interpersonal relationships by expressing respect, appreciation, and enthusiasm. Furthermore, it functions as a deep gratitude towards the Divine Father.